Retinal debris triggers cytotoxic damage in cocultivated primary porcine RPE cells - Wagner, Natalie; Tsai, Teresa; Reinehr, Sabrina; Theile, Janine; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Neuroscience, 2024)
One of the most common causes of vision loss in the elderly population worldwide is agerelated macular degeneration (AMD). Subsequently, the number of people affected by AMD is estimated to reach approximately 288 million by the year 2040. The aim of this study was to develop an ex vivo model that simulates various aspects of the complex AMD pathogenesis. For this purpose, primary porcine retinal pigment epithelial cells (ppRPE) were isolated and cultured. One group was exposed to medium containing sodium iodate (NaIO3) to induce degeneration The others were exposed to different supplemented media, such as bovine serum albumin (BSA), homogenized porcine retinas (HPR), or rod outer segments (ROOS) for eight days to promote retinal deposits. Then, these ppRPE cells were cocultured with porcine neuroretina explants for eight days. To assess the viability of ppRPE cells, live/dead assay was performed at the end of the study. The positive RPE65 and ZO1 area was evaluated by immunocytochemistry and the expression of RLBP1, RPE65, and TJP1 was analyzed by RT-qPCR. Additionally, drusen (APOE), inflammation (ITGAM, IL6, IL8, NLRP3, TNF), oxidative stress (NFE2L2, SOD1, SOD2), and hypoxia (HIF1A) markers were investigated. The concentration of the inflammatory cytokines IL-6 and IL-8 was determined in medium supernatants from day 16 and 24 via ELISA. Live/dead assay suggest that especially exposure to NaIO3 and HPR induced damage to ppRPE cells, resulting in a significant ppRPE cell loss. All supplemented media resulted in decreased RPE-characteristic markers (RPE65; ZO-1) and gene expression like RLBP1 and RPE65 in the cultured ppRPE cells. Besides, some inflammatory, oxidative as well as hypoxic stress markers were altered in ppRPE cells cultivated with NaIO3. The application of HPR resulted in an enhanced APOE expression. Preexposure of the ppRPE cells led to a diminished number of cones in all supplemented media groups compared to CTRL. Overall, this novel coculture model represents an interesting initial approach to incorporating deposits into coculture to mimic AMD pathogenesis. Nevertheless, the effects of the media used need to be investigated in further studies.